Effect of secondary electron generation on dose enhancement in Lipiodol with and without a flattening filter. (15th February 2018) - Kawahara, Daisuke; Ozawa, Shuichi; Saito, Akito; Kimura, Tomoki; Suzuki, Tatsuhiko; Tsuneda, Masato; Tanaka, Sodai; Nakashima, Takeo; Ohno, Yoshimi; Murakami, Yuji; Nagata, Yasushi
Abstract: Purpose: Lipiodol, which was used in transcatheter arterial chemoembolization before liver stereotactic body radiation therapy (SBRT), remains in SBRT. Previous we reported the dose enhancement in Lipiodol using 10 MV (10×) FFF beam. In this study, we compared the dose enhancement in Lipiodol and evaluated the probability of electron generation (PEG) for the dose enhancement using flattening filter (FF) and flattening filter free (FFF) beams. Methods: FF and FFF for 6 MV (6×) and 10× beams were delivered by TrueBeam. The dose enhancement factor (DEF), energy spectrum, and PEG was calculated using Monte Carlo (MC) code BEAMnrc and heavy ion transport code system (PHITS). Results: DEFs for FF and FFF 6× beams were 7.0% and 17.0% at the center of Lipiodol (depth, 6.5 cm). DEFs for FF and FFF 10× beams were 8.2% and 10.5% at the center of Lipiodol. Spectral analysis revealed that the FFF beams contained more low‐energy (0–0.3 MeV) electrons than the FF beams, and the FF beams contained more high‐energy (>0.3 MeV) electrons than the FFF beams in Lipiodol. The difference between FFF and FF beam DEFs was larger for 6× than for 10×. This occurred because the 10× beams contained more high‐energy electrons. The PEGs for photoelectric absorption and Compton scattering for the FFF beams were higher than those for the FF beams. The PEG for the photoelectric absorption was higher than that for Compton scattering. Conclusions: FFF beam contained more low‐energy photons and it contributed to the dose enhancement. Energy spectra and PEGs are useful for analyzing the mechanisms of dose enhancement.